PENGARUH STORE ATMOSPHERE DAN VARIASI PRODUK TERHADAP MINAT PEMBELIAN ULANG - Faizin SPd MM, Muhammad (GEMA EKONOMI, 2020)
The research aims to examines and proves the influence of store atmosphere and product variations on the interest in repurchasing in the warunk upnormal branch Gresik. This research is important especially in store atmosphere which can influence the interest of repurchasing consumers and creating loyal consumers. This research uses quantitative approach with multiple linear regression. Amount of sample taken 84 respondents and data collection is done with a questionnaire to obtain data. Result of this research is that store atmosphere have positive significant influence to the interest in repurchasing in the warunk upnormal branch Gresik, and product variations have positive significant influence to the interest in repurchasing in the warunk upnormal branch Gresik.